Evaluation of sugar beet seed germination under salinity stress by a quick method - Samira Moghadam; Saeideh Maleki Farahani; Samar Khayamim (علوم و فناوری بذر ایران)
To evaluate the effect of salinity stress on seed germination and screening of sugar beet genotypes, 20 polygerm and 15 sugar beet drought tolerant genotypes were separately tested in between paper and rapid germination test in Erlen under control and 20 dSm-1. Also they were tested in rapid germination test in Erlen and green house experiment under control and 16 dSm-1 in factorial experiments based on completely randomized designs with four replicates. Salinity stress in rapid germination test decreased germination index over drought tolerant and polygerm sugar beet genotypes about 80 and 90%, respectively in comparison to normal. Rapid germination test in Erlen was found to be better and more suitable in comparison of sugar beet genotypes under salinity in comparison to between paper tests. Genotypes which had more field emergence potential in laboratory had more total dry weights in green house under salinity condition. There was positive and significant correlation between fast germination tests in EC=20 and 16 dSm-1, so it seems that the rapid germination method in Erlen in EC=16 dSm-1 is more efficient to evaluate sugar beet genotypes under saline conditions